Analysis of Gender Difference on Online Shopping Lifestyle at Padang City - Wiry Utami; Linda Wati; Listiana Sri Mulatsih (Profesional Muda Cendekia Publishing, 2021)
This study aimed to examine the gender difference between men and women in online shopping lifestyle at Padang City. This type of research is comparative study, carried out to compare the similarities and differences of two or more the fact and object properties in the framework based on certain carefully. The technique of taking sample is by using purposive sampling. Total sample in this study is 100 consist of 50 men and 50 women. The samples in this study were men and women consumers who have shopped online for at least the last six month. Data collection uses questionnaire and analysis methods using independent sample t-test. The result of this study show that there are no differences between men and women in online shopping lifestyle at Padang City by t sig value ( 0,442 )> 0,05.